I Can Only Paint The Story of Battlefield Artist Mary Riter Hamilton. - Gammel, Irene (McGill-Queen's/Beaverbrook Canadian Foundation Studies in Art History Ser., 2020)
For Mary Riter Hamilton, capturing the emotional landscape of battlefields and graveyards in the months after the Great War's armistice became an artistic calling and defined her work. This book recovers a body of work that stands as a unique and enduring portrait of the effects of the Great War.